2003
DOI: 10.1016/s0885-2014(02)00161-2
|View full text |Cite
|
Sign up to set email alerts
|

Situation bounded conceptual organization in children: from action to spatial relations

Abstract: This study performed on children aged 5, 8, and 10 years, deals with conceptual knowledge organization using a word association task. The results show that, at all these ages, the production of thematic relations outnumbers that of taxonomic relations; no thematic-to-taxonomic shift occurs. While children aged 5 years produce more action, temporal, and event relations, older children produce more spatial and property relations. An increased capacity for abstraction allows children aged 8 and 10 years to captur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
32
0
9

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 20 publications
1
32
0
9
Order By: Relevance
“…Thematic relations (e.g., spoon-yoghurt) are based on contextual and functional relations between objects that can be easily detected from interactions with objects in daily action schemas (Borghi & Caramelli, 2003;Mandler, 2000;Nelson, 1983). Therefore, thematic relations appear to be more rapidly identified for objects that particularly induce action and use experience-namely, manipulable objects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thematic relations (e.g., spoon-yoghurt) are based on contextual and functional relations between objects that can be easily detected from interactions with objects in daily action schemas (Borghi & Caramelli, 2003;Mandler, 2000;Nelson, 1983). Therefore, thematic relations appear to be more rapidly identified for objects that particularly induce action and use experience-namely, manipulable objects.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies in children have already shown that perceptual similarity and contextual/functional relations underlie conceptual development (Bonthoux & Kalé nine, 2007;Borghi & Caramelli, 2003;Kemler Nelson, Frank enfield, Morris, & Blair, 2000;Nelson, 1983;Quinn & Eimas, 2000;Sloutsky et al, 2007). The present study further demonstrates that, for children from age 5, perceptual and contextual/functional information is accessible differently for manipulable and nonmanipulable object concepts.…”
Section: Analysis Of Children's Performancementioning
confidence: 97%
“…The general consensus is that taxonomic and thematic relations rely on two functionally distinct, but complementary, modes of conceptual organization in semantic memory. The dissociation of taxonomic versus thematic processing has been documented in behavioral (Borghi & Caramelli, 2003;Lin & Murphy, 2001;Masuda & Nisbett, 2001;Mirman & Graziano, 2012), neuroimaging (Kalénine, Mirman, & Buxbaum, 2012;Sachs, Weis, Krings, Huber, & Kircher, 2008;Schwartz et al, 2011), and patient (Davidoff & Roberson, 2004) studies. Furthermore, thematic processing has been shown to be as crucial in language comprehension, analogy making, similarity judgment, and memory processes as is taxonomic knowledge (for a review, see Estes et al, 2011).…”
mentioning
confidence: 98%
“…The proposed classification is not exhaustive and does not include all possible types of thematic relations identified in prior research (Borghi & Caramelli, 2003;Estes, Golonka, & Jones, 2011). Furthermore, currently there is not general agreement about a comprehensive typology of thematic relations (for a discussion, see McRae, Khalkhali, & Hare, 2012).…”
mentioning
confidence: 99%
“…Studies have shown that thematic relations govern young children's memory than taxonomic categories [2,13,[24][25][26]. Other studies have reported that, children are able to flexibly use both thematic and taxonomic relations with no pervasive preference for either mode of response [27,28].…”
Section: Introductionmentioning
confidence: 99%